Development and validation of a stability-indicating RP-HPLC method of cholecalciferol in bulk and pharmaceutical formulations: Analytical quality by design approach - Dilipkumar Suryawanshi, Durgesh Kumar Jha, Umesh Shinde, Purnima D. Amin (Journal of Applied Pharmaceutical Science, 2019)
The present article utilized analytical quality by design (AQbD) methodology to optimize chromatographic conditions for the routine analysis of Cholecalciferol (CHL). Taguchi orthogonal array design and Box–Behnken design were employed to screen and optimize critical method parameters for augmenting the method performance. The optimal chromatographic separation was attained on Eurosphere® 100-5, C8 (250 × 4.6 mm i.d., 5 μm) column in an isocratic elution mode using methanol:acetonitrile (50:50, % v/v) as mobile phase at a flow rate of 1.0 ml/minutes and photodiode array detection at 265 nm. The optimized chromatographic method was successfully validated as per International Council for Harmonisation Q2 (R1) guidelines. The method was found to be linear (r2 = 0.9993) in the range of 20–100 IU/ml. Limit of detection and limit of quantitation were found to be 10 and 20 IU/ml. The precision, robustness, and ruggedness values were within the acceptance limits (relative standard deviation < 2). The percent recovery of in-house developed 400 IU mouth dissolving tablets and marketed Tayo 60k tablets were found to be 99.89% and 101.46%, respectively. The forced degradation products were well resolved from the main peak suggesting the stability-indicating the power of the method. In conclusion, the AQbD-driven method is highly suitable for analysis of CHL in bulk and pharmaceutical formulations.
Keywords: Cholecalciferol, analytical quality by design, Taguchi orthogonal array design, Box–Behnken design, method validation, forced degradation studies.